Dark septate endophyte Exophiala pisciphila promotes maize growth and alleviates cadmium toxicity - Wang, Lei; Li, Zuran; Zhang, Guangqun; Liang, Xinran; Hu, Linyan; Li, Yuan; He, Yongmei; Zhan, Fangdong (Frontiers in Microbiology, 2023)
Dark septate endophytes (DSE) are typical root endophytes with the ability to enhance plant growth and tolerance to heavy metals, but the underlying mechanisms are unclear. Here, the physiological and molecular mechanisms of a DSE strain, Exophiala pisciphila, in mitigating cadmium (Cd, 20 mg/kg) toxicity in maize were investigated. Our results showed, under Cd stress, E. pisciphila inoculation enhanced the biomass of maize and reduced both inorganic and soluble forms of Cd (high toxicity) by 52.6% in maize leaves, which may be potentially contributing to Cd toxicity mitigation. Besides, E. pisciphila inoculation significantly affected the expression of genes involved in the signal transduction and polar transport of phytohormone, and then affected abscisic acid (ABA) and indole-3-acetic acid (IAA) contents in maize roots, which was the main reason for promoting maize growth. In addition, E. pisciphila also made a 27% increase in lignin content by regulating the expression of genes involved in the synthesis of it, which was beneficial to hinder the transport of Cd. In addition, E. pisciphila inoculation also activated glutathione metabolism by the up-regulation of genes related to glutathione S-transferase. This study helps to elucidate the functions of E. pisciphila under Cd stress, sheds light on the mechanism of detoxifying Cd and provides new insights into the protection of crops from heavy metals.